(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25^2 -1)(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25-(a.b^2-a) với a= -1 , b=(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25 25(a^2 +b^2 -1)-(a.b^2(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25-a) với a= -1 (a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25=5 25
Biến đổi tương đương ta có
\(\frac{a^2}{b^2}+\frac{b^2}{a^2}-\frac{a}{b}-\frac{b}{a}\ge0\)
\(\Leftrightarrow\frac{a^4+b^4-a^3b-ab^3}{a^2b^2}\ge0\)
\(\Leftrightarrow a^4+b^4-a^3b-ab^3\ge0\)
\(\Leftrightarrow a^4+b^4-2a^2b^2+2a^2b^2-a^3b-ab^3\ge0\)
\(\Leftrightarrow\left(a^2-b^2\right)^2-ab\left(a^2-2ab+b^2\right)\ge0\)
\(\Leftrightarrow\left(a-b\right)^2\left(a+b\right)^2-ab\left(a-b\right)^2\ge0\)
\(\Leftrightarrow\left(a-b\right)^2\left(\left(a+b\right)^2-ab\right)\ge0\)
\(\Leftrightarrow\left(a-b\right)^2\left(a^2+ab+b^2\right)\ge0\) (Luôn đúng)